If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12+2+6x-2=90
We simplify the equation to the form, which is simple to understand
12+2+6x-2=90
We move all terms containing x to the left and all other terms to the right.
+6x=+90-12-2+2
We simplify left and right side of the equation.
+6x=+78
We divide both sides of the equation by 6 to get x.
x=13
| -5(-6x-8)+7(4x-4)=12 | | -13=-5k-8k | | -18+4+x=9 | | -18+4+x=9 | | A+z=b | | 8m+7m=16 | | -13=-4 | | 14m-10=3(4x-2) | | 3-2x+5=12 | | 12x+42=20x+18 | | -2x+1=4 | | 250=9g+14w | | 12b^3-2b-30b=0 | | n*2*9=49 | | 240=11g+4w | | 7x=4-3(x-1) | | 3x+11=7x+3 | | 6(y-3)=24 | | 240=4w+11g | | x+7-3x=16-5x+3 | | 1.2x=.72 | | 5x-20+3=7x | | 4=7w+6 | | 4x+6=2(x+8) | | 3x=7x-20 | | 7x-3=5-2x | | 3x-2x+1=x+6 | | 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 |